Alignment of Assessment Objectives with Instructional Objectives Using Revised Bloom's Taxonomy—The Case for Food Science and Technology Education - Jideani, V. A.; Jideani, I. A. (Journal of food science education, 2012)
:  Nine food science and technology (FST) subjects were assessed for alignment between the learning outcomes and assessment using revised Bloom's taxonomy (RBT) of cognitive knowledge. Conjoint analysis was used to estimate the utilities of the levels of cognitive, knowledge, and the attribute importance (cognitive process and knowledge dimension) for learning outcomes and assessments. Lecturers for these subjects produced learning outcomes for ability of students to Understand (4.935) Procedural (3.316) as well as Apply (4.491) Conceptual (3.083) knowledge. Lecturers’ expected students’ to move beyond mere recall and recognition of knowledge to higher order cognitive knowledge of apply, analyze, evaluate, and create. However, the assessments tested students’ ability to Understand (4.791) Conceptual (4.168) as well as Remember (3.217) Procedural (0.581) knowledge resulting in a misaligned teaching and learning exercise. For all the subjects, emphasis was more (52.9% to 72.9%) on the cognitive dimension than on forms of knowledge in formulating the learning outcomes, whereas emphasis placed on the cognitive (33.3% to 62.5%) dimension and the knowledge (37.5% to 66.7%) forms in the questions differed from subject to subject. The cognitive weight in the assessment was more for Understand (1.781)/Remember (0.787) Conceptual (1.416) knowledge. RBT provides an assessment framework that can be used to assist instructors in going beyond factual knowledge and comprehension to include academic skills such as application, analysis, evaluation, and creation.